1999
DOI: 10.1038/sj.bjp.0702264
|View full text |Cite
|
Sign up to set email alerts
|

Long term orexigenic effect of a novel melanocortin 4 receptor selective antagonist

Abstract: 1 We designed and synthesized several novel cyclic MSH analogues and tested their a nities for cells expressing the MC1, MC3, MC4 and MC5 receptors. 2 One of the substances HS028 (cyclic [AcCys 11 , dichloro-D-phenylalanine 14 , Cys 18 , Asp-NH 2 22 ]-b-MSH 11 ± 22 ) showed high a nity (Ki of 0.95nM) and high (80 fold) MC4 receptor selectivity over the MC3 receptor. HS028 thus shows both higher a nity and higher selectivity for the MC4 receptor compared to the earlier ®rst described MC4 receptor selective subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 30 publications
3
39
0
1
Order By: Relevance
“…The control rats were affected by the surgical operation associated with implantation of the osmotic pumps as indicated by a modest reduction in food intake and weight loss during the first week of treatment. The reduced food intake caused by the operation was blocked by the selective MC4 antagonist HS024, which is in agreement with earlier data from a 1-week study on HS028 (Skuladottir et al 1999) and a 2-week study on HS014 (Kask et al 1999), both substances being MC4 antagonists. This is also in agreement with previous results showing that immobilisation-induced anorexia was reversed by administration of the selective MC4 receptor antagonist HS014 (Vergoni et al 1999).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The control rats were affected by the surgical operation associated with implantation of the osmotic pumps as indicated by a modest reduction in food intake and weight loss during the first week of treatment. The reduced food intake caused by the operation was blocked by the selective MC4 antagonist HS024, which is in agreement with earlier data from a 1-week study on HS028 (Skuladottir et al 1999) and a 2-week study on HS014 (Kask et al 1999), both substances being MC4 antagonists. This is also in agreement with previous results showing that immobilisation-induced anorexia was reversed by administration of the selective MC4 receptor antagonist HS014 (Vergoni et al 1999).…”
Section: Discussionsupporting
confidence: 81%
“…The peptides were dissolved in ACSF and infused at 0·25 µl/h. The selection of drug infusion rate (0·1 nmol/h) was based on previous experience (Haynes et al 1999, Kask et al 1999, Skuladottir et al 1999. The infusions were made with an osmotic minipump (Alzet, model 2004; Alza Corp., Palo Alto, CA, USA) which had first been activated by immersion in 0·9% saline at room temperature for 12 h before implantation.…”
Section: Implantation Of Pumpsmentioning
confidence: 99%
“…Tachyphylaxis to HS028 did not occur. However, neither energy expenditure nor pituitary function were examined in this study (17). Previous results from this department have demonstrated that AGRP (83-132), the endogenous hypothalamic melanocortin receptor antagonist, significantly increased 24-h food intake and antagonized the anorectic effects of ␣-MSH (16).…”
mentioning
confidence: 84%
“…A prominent role for the MC 4 R was highlighted by MC 4 R knockout mice, which exhibited maturity-onset obesity, overeating, hyperinsulinemia, and increased linear growth (Huszar et al 1997). The role of the MC 4 R in body weight regulation was further confirmed by pharmacologic studies showing that MC 4 R agonists suppress food intake and antagonists increase food intake (Kask et al 1998a;Murphy et al 1998;Skuladottir et al 1999). These studies led ultimately to the discovery of mutations in the melanocortin system in obese humans (Krude et al 1998).…”
Section: Animal Models Of Obesitymentioning
confidence: 99%